Fetal Medicine Foundation fetal and neonatal population weight charts. (30th May 2018) - Nicolaides, K. H.; Wright, D.; Syngelaki, A.; Wright, A.; Akolekar, R.
ABSTRACT: Objective: To develop fetal and neonatal population weight charts. The rationale was that, while reference ranges of estimated fetal weight (EFW) are representative of the whole population, the traditional approach of deriving birth‐weight (BW) charts is misleading, because a large proportion of babies born preterm arise from pathological pregnancy. We propose that the reference population for BW charts, as in the case of EFW charts, should comprise all babies at a given gestational age, including those still in utero . Methods: Two sources of data were used for this study. For both, the inclusion criteria were singleton pregnancy, dating by fetal crown–rump length at 11 + 0 to 13 + 6 weeks' gestation, availability of ultrasonographic measurements of fetal head circumference (HC), abdominal circumference (AC) and femur length (FL) and live birth of phenotypically normal neonate. Dataset 1 comprised a sample of 5163 paired measurements of EFW and BW; ultrasound examinations were carried out at 22–43 weeks' gestation and birth occurred within 2 days of the ultrasound examination. EFW was derived from the HC, AC and FL measurements using the formula reported by Hadlock et al. in 1985. Dataset 2 comprised a sample of 95 579 pregnancies with EFW obtained by routine ultrasonographic fetal biometry at 20 + 0 to 23 + 6 weeks' gestation ( n = 45 034), 31 + 0 to 33 + 6 weeks ( n = 19 224) or 35 + 0 to 36 + 6 weeks ( n = 31 321); for the purpose of this study we included data for only one of the three visits per pregnancy. In the development of reference ranges of EFW and BW according to gestational age, the following assumptions were made: first, that EFW and BW have a common median, dependent on gestational age; and second, that deviations from the median occur in both EFW and BW and these deviations are correlated with different levels of spread for EFW and BW, dependent on gestational age. We adopted a Bayesian approach to inference, combining information from the two datasets using Markov Chain Monte‐Carlo sampling. The fitted model assumed that the mean log transformed measurements of EFW and BW are related to gestational age according to a cubic equation and that deviations about the mean follow a bivariate Gaussian distribution. Results: In the case of EFW in Dataset 2, there was a good distribution of values < 3 rd, < 5 th, < 10 th, > 90 th, > 95 th and > 97 th percentiles of the reference range of EFW according to gestational age throughout the gestational age range of 20 + 0 to 36 + 6 weeks. In the case of BW, there was a good distribution of values only for the cases delivered > 39 weeks' gestation. For preterm births, particularly at 27–36 weeks, BW was below the 3 rd, 5 th and 10 th percentiles in a very high proportion of cases, particularly in cases of iatrogenic birth. The incidence of small‐for‐gestational‐age fetuses and neonates in the respective EFW and BW charts was higher in women of black than those of white racial origin. Conclusion: We established a BW chart for all babies at a given gestational age, including those still in utero, thereby overcoming the problem of underestimation of growth restriction in preterm birth. BW and EFW charts have a common median but differ in the levels of spread from the median. Copyright © 2018 ISUOG. Published by John Wiley & Sons Ltd. Abstract : This article's abstract has been translated into Spanish and Chinese. Follow the links from theabstract to view the translations. This article has been selected for Journal Club. Clickhere to view slides and discussion points.